The Differences of Lipoprotein-Associated Phospholipase A2, Apolipoprotein B and Low Density Lipoprotein In Obese and Lean Men - Yuliana Yuliana; Purwanto Adipireno; Edward Kurnia Setiawan Limijadi; Nyoman Suci Widyastiti; Dwi Retnoningrum (Faculty of Medicine, Diponegoro University, 2021)
ABSTRACT Background: An increase in fat accumulation in obesity has been suggested to link with an increase in inflammation. This inflammation may be associated with an elevated of Lipoprotein-Associated Phospholipase A2 (Lp-PLA2), Apolipoprotein B (Apo B), and Low-Density Lipoprotein (LDL), thereby associated with the risk of atherosclerosis.Objective: To investigate the differences between Lp-PLA2, Apo B, and LDL levels in obese and lean men.Methods: A cross-sectional study was conducted on 74 men (obese and lean) at the Faculty of Medicine, Diponegoro University, Indonesia, in 2020. The concentration of LDL was measured using the homogenous enzymatic colourimetric method, whereas the levels of Lp-PLA2 and Apo B were determined using the ELISA method. Data were analyzed using an Independent t-test, setting statistical significance at p <0.05.Results: This study showed that Lp-PLA2 levels were significantly different between obese and lean men (p = 0.039). Furthermore, LDL levels were also significantly different between obese and lean men (p = 0.002). However, we did not find any differences in Apo B between obese and lean men (p = 0.640).Conclusion: Lp-PLA2 and LDL levels were slightly higher in obese compared to lean men, but no difference of Apo B.